A Learning Trajectory for Understanding Negative Integers through the Context of the E-Comic-Based Jejamok Game - Ratih Handayani; Ratu Ilma Indra Putri; Zulkardi; Darmawijoyo (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2026)
Understanding the concept of negative integers and their properties remains a challenge for elementary school students. This challenge is related to their abstract nature and lack of strong roots in everyday experience. This study aims to design a learning trajectory for negative integers through the context of the traditional game Jejamok, presented in the form of E-comic. This allows students to construct the meaning of negative numbers gradually and meaningfully to discover the properties of integers. The study employed a design research approach with three main stages: preparation, learning experiments, and retrospective analysis to revise the Hypothetical Learning Trajectory. The subjects were sixth-grade students at Soekarno-Hatta Elementary School in North Lampung who used E- comic based on the game Jejamok, student activity sheets, and pre-post diagnostic tests. The results revealed a learning trajectory consisting of five interconnected activities: (1) contextual experience through gameplay, (2) compiling scores using positive and negative numbers, (3) discussion of meaning to interpret integers and zero, (4) formulation of operations using symbols and number lines, and (5) application to explore integer properties. These activities support students in progressing from informal reasoning to formal mathematical understanding. The integration of the Jejamok context with e-comic media enhances students’ engagement and provides meaningful support for conceptual development. This study contributes to the development of culturally responsive and digitally supported learning trajectories for teaching abstract mathematical concepts.